ANALISIS KUALITAS AIR SUNGAI KIKIM DI KECAMATAN KIKIM TIMUR KABUPATEN LAHAT - Ahmad Walid; Fadila Turahmah; Pisi Ismarliana (EKOLOGIA, 2020)
This study aims to determine the physical properties of Kikim River water in Kikim Timur Subdistrict, Lahat Regency and find out the right way to solve water problems as an effort to treat water from physical parameters that exceed the quality standards according to the Regulation of the Minister of Health of the Republic of Indonesia Number 492 / MENKES / PER / IV / 2018 concerning requirements for drinking water quality. The parameters tested in this study included temperature, total suspended solid (TSS) and degree of acidity (pH). Sampling was carried out at three points, namely Point 01 in Gunung Kembang Village or Kikim Hulu River, Point 02 in Bungamas Village or Kikim Tengah River, and Point 03 in Lubuk Tampang Village or Kikim Hilir River. The results of the test analysis of the Kikim Timur River water samples carried out at the Environmental Service Unit of the Environmental Service Laboratory (DLH) of Lahat Regency at points 01, 02 and 03 indicate that the parameters tested, namely temperature, (TSS) and pH values still meet the standards according to Regulation of the Minister of Health of the Republic of Indonesia Number 492 / MENKES / PER / IV / 2018.